2021
DOI: 10.3389/fcell.2021.685522
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Reverses Hashimoto’s Thyroiditis by Regulating Key Immune Events

Abstract: BackgroundHashimoto’s thyroiditis (HT) is a common autoimmune disease characterized by high levels of thyroid peroxidase antibody (TPOAb) and thyroid globulin antibody (TgAb) as well as infiltration of lymphocytes in thyroid. In recent years, metformin has been proven to be effective in a variety of autoimmune diseases, such as systemic lupus erythematosus, rheumatoid arthritis and multiple sclerosis.MethodsThis study systematically explored the therapeutic effect of metformin on HT and its underlying mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Besides, we also performed GSEA analysis of macrophage polarization in mouse thyroid tissue. mRNA-seq data were obtained from our previous study ( 34 ), including normal controls (n=3) and thyroiditis model group (n=5). GSEA results showed that M1 polarization characteristic gene set was significantly enriched in the thyroiditis group (ES=0.63, P<0.001, FDR q<0.001), while M2 was not (ES=0.38, P<0.001, FDR q<0.001) ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, we also performed GSEA analysis of macrophage polarization in mouse thyroid tissue. mRNA-seq data were obtained from our previous study ( 34 ), including normal controls (n=3) and thyroiditis model group (n=5). GSEA results showed that M1 polarization characteristic gene set was significantly enriched in the thyroiditis group (ES=0.63, P<0.001, FDR q<0.001), while M2 was not (ES=0.38, P<0.001, FDR q<0.001) ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a mouse thyroiditis model was constructed by high iodine water feeding and thyroglobulin immuno-injection, which was described in our previous study in detail ( 34 ). Female 6–8 weeks old C57BL/6 mice from Shanghai Model Organisms Center were kept at the SPF level and free to eat and drink.…”
Section: Methodsmentioning
confidence: 99%
“…Optimization of the INS protocol for splenic neutrophil isolation could be applied to obtain untouched splenic neutrophils; however, it could be rather expensive because of the complex cocktail of antibodies that should be added to the splenocyte suspension along with the EasySep antibody cocktail [24]. Taking into account the low content of neutrophils in the spleen of healthy mice [24][25][26] and obtained data on purity/viability of cells (Table 2) the IPS protocol is recommended for splenic neutrophil isolation.…”
Section: Comparison Of Purity Viability and Yield Of Neutrophil Sampl...mentioning
confidence: 99%
“…Morphological changes of thyroid were observed by an experienced technician using a BX53F optical microscope (Olympus, Tokyo, Japan) at 200× magnification. The percentage of lymphocytic infiltration area was analyzed using Image-Pro Plus 6.0 software (Media Cybernetics, Silver Spring, MD, USA) (16,17).…”
Section: Morphological Observationmentioning
confidence: 99%